Incidence of Liver Cirrhosis in Infancy and Childhood (Medical Forum Monthly, 2024)
Cirrohsis is the end result of chronic liver disease caused by the different pathological factors including congenital malformation, inflammation (hepatitis) and metabolic / storage disorders, leading to liver cell damage. To determine the incidence of liver cirrhosis in infancy and childhood with chronic hepatitis, we studied 41 biopsies of children for the presence of cirrhosis. Objectives: To provide an overview of current childhood statistics of hepatitis and liver cirrhosis to facilitate analysis of the impact of past research discoveries on outcome and provide essential information for prioritizing future research directions.Study Design: Retrospective Study.Place and Duration of Study: This study was conducted at the Department of Basic Medical Sciences Institute, JPMC, Karachi from Jan. 2000 to Dec. 2007.Materials and Methods: Slides / paraffin blocks of liver biopsies from patients under 15 years of age. The cases were of two categories i.e. retrospective & prospective. The distribution of 41 cases of hepatitis was according to Age & Sex. Total 22 (53.7%) cases were encountered in the youngest of 0-5 years age group, 13 (13.7%) cases in 6-10 years and only 6 (14.6%) cases in 11-15 years age group.Results: The distribution of 41 cases of cirrhosis of liver, according to age & sex . the maximum 22 (53.77 % ) youngest case in 0-5 years ,13 (31.7%) cases in 6-10 years & 6 (14.6%) cases were found in 11-15 year age group.Conclusion: It is observed that the tendency of liver inflammation was decreased with increasing age and sexual differentiation shows male predominance with male to female ratio of 2.4:1. Liver cirrhosis discovered with increasing age in children. It is found to be a common cause for enlargement of liver with associated hepatitis and chronic liver diseases in infants and children. It can lead to higher risks of acute or chronic responses in adulthood and will require new treatment paradigms building on an increased understanding of the molecular processes for infancy and childhood liver cirrhosis.